Fenomenologi Bahasa Komunitas Kampung Arab (Studi Kasus Alih Kode dan Campur Kode Percakapan Bahasa Arab di Ampel Surabaya): Phenomenology of Arabic Village Community Language (Case Study of Code Switching and Arabic Conversation Code Mixing in Ampel Surabaya) - Dewien Nabielah Agustin (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2021)
The language of the Arab community is unique when it comes to the style of language and how people interact. People of Arab ethnic descent are generally classified as bilingual societies. They mastered the first language (B1) regional language and the second language (B2) Arabic. This study aims to determine the speech used by the ethnic community of Arab descent Ampel in the city of Surabaya. The approach used in this research is a qualitative approach. In this study it can be concluded that first, the form of code switching in Arab community communication includes code switching from Arabic to Indonesian and code switching from Indonesian to Arabic; Second, the form of code mixing is the insertion of words, phrases and clauses; Third, the factors that cause code switching and code mixing are the speaker, the interlocutor, the presence of a third speaker, the mode of conversation and the topic of discussion; Fourth, the purpose and function of code switching and code mixing in Arab community communication is to familiarize the atmosphere, evoke a sense of humor, look prestigious, respect the interlocutor and tell secrets.